Gage d'une paix durable : la frontière occidentale de la Pologne - Demuyter, Ernest; Crouquet, Roger; Duwaerts, Léon; Hauptman, Jan (Bruxelles: Amitiés Belgo-Polonaises)
"Ernest Demuyter ; Roger Crouquet, Léon Duwaerts, Jan Hauptman, ... et al. Bibliotheek François Vercammen"